Creatine monohydrate administration delayed muscle glycolysis of antemortem-stressed broilers by enhancing muscle energy status, increasing antioxidant capacity and regulating muscle metabolite profiles - Ning Liu; Qingzhen Zhong; Zewei Sun; Bolin Zhang (Poultry Science)
Preslaughter stress induced a negative energy balance of broilers, resulted in an accelerated glycolysis and finally led to an inferior meat quality. The present study aimed to investigate the effects of creatine monohydrate (CMH) supplementation on muscle energy storage, antioxidant capacity, the glycolysis of postmortem muscle and the metabolite profiles in muscle of broilers subjected to preslaughter transport. Two hundred and forty broilers were chosen and randomly allocated into three treatments (group A, group B and group C), comprising 8 replicates (10 broilers each replicate). Broilers in group A and B as well as group C were fed with the basal diet or diets containing 1200 mg/kg CMH for 14 days, respectively. After 12 h feed deprivation, broilers in group B (T3h group) and group C (T3h +CMH1200 group) were both subjected to a preslaughter transportation (3 h), but those in group A were treated with a 0.5 h-transport (refined as the control group). The results showed that preslaughter stress led to a lower pH24 h value, a bigger L* value and a higher drip loss of muscle compared with the control group (P < 0.05). In addition, transport stress accelerated glycolysis in postmortem muscle, decreased energy storage and the antioxidant capacities of muscle (P < 0.05). However, CMH administration ameliorated energy status, delayed muscle glycolysis, elevated mRNA expression involved in Cr metabolism and inhibited AMPK signaling of broilers experienced preslaughter transport stress. Moreover, significant differences in glycine, serine and threonine metabolism, cysteine and methionine metabolism, purine metabolism, arginine and proline metabolism, ABC transporters, carbon metabolism, lysine metabolism and sulfur metabolism were observed using pathway enrichment analysis. Additionally, the contents of Cr and ATP were positively correlated with branched amino acids (L-valine and l-leucine), l-asparagine, inosine, PCr and d-ribose by metabolomics analysis. Taken together, CMH ameliorated energy status, delayed muscle glycolysis and improved meat quality of antemortem-stressed broilers by the regulation of pathways and key metabolites involved in energy metabolism of postmortem muscle.